Whole Grain Rye Intake, Reflected by a Biomarker, Is Associated with Favorable Blood Lipid Outcomes in Subjects with the Metabolic Syndrome – A Randomized Study - Magnusdottir, Ola Kally; Landberg, Rikard; Gunnarsdottir, Ingibjorg; Cloetens, Lieselotte; Åkesson, Björn; Rosqvist, Fredrik; Schwab, Ursula; Herzig, Karl-Heinz; Hukkanen, Janne; Savolainen, Markku J.; Brader, Lea; Hermansen, Kjeld; et al. (PloS one, 2014)
Few studies have explored the possible plasma cholesterol lowering effects of rye consumption. The aim of this secondary analysis in the SYSDIET study was to investigate the association between plasma alkylresorcinols (AR), a biomarker for whole grain wheat and rye intake, and blood lipid concentrations in a population with metabolic syndrome. Furthermore, we analyzed the associations between the AR C17:0/C21:0 ratio, a suggested marker of the relative intake of whole grain/bran rye, and blood lipid concentrations. Participants were 30-65 years of age, with body mass index (BMI) 27-40 kg/m2 and had metabolic syndrome. Individuals were recruited through six centers in the Nordic countries and randomized either to a healthy Nordic diet (ND, n = 93), rich in whole grain rye and wheat, as well as berries, fruits and vegetables, rapeseed oil, three fish meals per week and low-fat dairy products, or a control diet (n = 65) for 18/24 weeks. Associations between total plasma AR concentration and C17:0/C21:0 homologue ratio and blood lipids were investigated in pooled (ND + control group) regression analyses at 18/24 weeks adjusted for baseline value for the dependent variable, age, BMI and statin use. When adjusted for confounders, total plasma AR at 18/24 weeks was not significantly associated with blood lipids but the AR ratio C17:0/C21:0 was inversely associated with LDL cholesterol concentrations (B (95% CI): -0.41 (-0.80 to -0.02)), log LDL/HDL cholesterol ratio (-0.20 (-0.37 to -0.03)), log non-HDL cholesterol (-0.20 (-0.37 to -0.03)), log apolipoprotein B (-0.12 (-0.24 to 0.00)) and log triglyceride concentrations (-0.35 (-0.59 to -0.12)). Increased proportion of whole grain rye, reflected by a biomarker, in the diet is associated with favorable blood lipid outcomes, a relationship that should be further investigated. ClinicalTrials.gov NCT00992641.